Evaluación morfo-agronómica y productiva de 12 cultivares de Soya (Glycine Max L. Merril) en la parroquia Ricaurte, cantón Urdaneta, provincia Los Ríos - Luiz Yuguay, Edwin Clemente (2017)
The Soya is considered in the modern world agriculture as one of the most profitable crops. Soybean production predominates in America with an annual average of 172'885.867 Tm over the last decade. The objectives of this research were to determine the main morpho-agronomic characteristics of 12 soybean cultivars. Select soybean cultivars based on their performance potential. Establish a database of morpho-agronomic characterization of 12 soybean cultivars, to continue the process of research. In the canton Urdaneta there is low productivity of soybean mainly due to the lack of improved, adapted and available to the farmer, poor seed quality by recycling and inadequate crop management, varieties so obtaining new cultivars is necessary with high yield potential. This research will contribute to validate and generate new varieties with improved agronomic characteristics, such as adaptation and performance; besides having qualitative and quantitative information on new soybean genotypes which subsequently may be released as commercial varieties. The research was conducted in the Ricaurte of canton Urdaneta, provincia Los Rios. The used 12 soybean cultivars from INIAP used a design randomized complete block (RCBD) and an analysis of variance ANOVA was used. Based on the analysis and interpretation of the results obtained in this trial, the variety INIAP-310 reached the highest yield 5364.47 kg/ha. The 12 treatments evaluated in this trial showed morphological and agronomically considered within the required demand for soybeans, also showed resistance and tolerance to pesticides and flattens problems. In this research, the best performance was due to increased: Loading height (AC) with 84%, branches per plant (RP) with 91 %, pods per plant (VP) with 92 % and grains per plant (GP) 92 %. The variety with better yield potential, selected for this agro-ecological zone and planting time of May 27, 2015 was: INIAP-310.